Differential contributions of cortical thickness and surface area to trait impulsivity in healthy young adults - Kubera, Katharina Maria; Schmitgen, Mike; Maier-Hein, Klaus H.; Thomann, Philipp; Hirjak, Dusan; Wolf, Robert Christian (Behavioural brain research, 2018)
Background - Impulsivity is an essential human personality trait and highly relevant for the development of several mental disorders. There is evidence that impulsivity is heritable, yet little is known about neural correlates reflecting early brain development. Here, we address the question whether motor, attentional and non-planning components, as reflected by the Barratt Impulsiveness Scale (BIS-11), are distinctly associated with cortical thickness and surface area variations in young healthy individuals. - Method - We investigated cortical thickness and surface area in 54 healthy volunteers (m/f=30%/70%; age mean/SD=24.9/4.02) using structural magnetic resonance imaging at 3T together with surface-based analysis techniques. Impulsivity was examined on the Barratt impulsiveness scale (BIS-11) and related to the two distinct cortical measurements. - Results - Higher BIS-11 total scores were negatively associated with cortical thickness variations in the left lingual gyrus, left superior temporal gyrus, right cuneus, and right superior parietal gyrus (p<0.05 cluster-wise probability [CWP] corrected). Higher BIS-11 nonplanning scores were negatively associated with cortical thickness variations in bilateral pericalcarine gyrus (p<0.05 CWP corr.). In the orbitofrontal cortex, the association between impulsivity and cortical thickness differed significantly between males and females. - Conclusion - These data suggest distinct neurodevelopmental trajectories underlying impulsivity in healthy subjects. Impulsivity total scores appear to be specifically related to cortical thickness variations, in contrast to variations of cortical surface area. Furthermore, our findings underscore the importance of better characterizing gender-specific structural correlates of impulsivity.